(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2009)
The engraved mirror recovered from the Calvario tomb 1709, within the Monterozzi necropolis of ancient Tarquinia, is likely to refer to one of the ateliers of S. Francisco Group: the reflecting surface probably represents two Homeric heroes, Achilles and Aiax; this object is an important evidence both for the iconographic analysis and, in association with the other grave-goods, for the study of the funerary Selbstdarstellung strategies of the renovate Tarquinian society of the 4-3rd century B.C.